2013
DOI: 10.1007/s00125-013-2917-x
|View full text |Cite
|
Sign up to set email alerts
|

Cause-specific mortality in Scottish patients with colorectal cancer with and without type 2 diabetes (2000–2007)

Abstract: Aims/hypothesis The objective of this study was to use Scottish national data to assess the influence of type 2 diabetes on (1) survival (overall and cause-specific) in multiple time intervals after diagnosis of colorectal cancer and (2) cause of death. Methods Data from the Scottish Cancer Registry were linked to data from a population-based national diabetes register. All people in Scotland diagnosed with nonmetastatic cancer of the colon or rectum in 2000-2007 were included. The effect of pre-existing type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
3
13
0
1
Order By: Relevance
“…In our meta-analysis, year of publication ranged from 2003 to 2016, and the regions included 2 American countries[7, 1315, 18, 19, 27, 30, 33, 37, 41, 42, 45, 46], 6 European countries[6, 11, 17, 28, 32, 39, 40, 44], 2 Asian countries[8, 9, 12, 16, 20, 29, 3436, 38, 43, 47] and 1 Oceania country[31]; the included studies contained 15 retrospective[9, 10, 14, 16–20, 27, 33, 36, 37, 39, 41, 47] and 21 prospective[68, 1113, 15, 2832, 34, 35, 38, 40, 4246] cohort studies; the sample size ranged from 391 to 1056243, and the mean age of study ranged from 46.4 to 72.07. In DM ascertainment, 25 studies[6, 8, 9, 1115, 18, 19, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our meta-analysis, year of publication ranged from 2003 to 2016, and the regions included 2 American countries[7, 1315, 18, 19, 27, 30, 33, 37, 41, 42, 45, 46], 6 European countries[6, 11, 17, 28, 32, 39, 40, 44], 2 Asian countries[8, 9, 12, 16, 20, 29, 3436, 38, 43, 47] and 1 Oceania country[31]; the included studies contained 15 retrospective[9, 10, 14, 16–20, 27, 33, 36, 37, 39, 41, 47] and 21 prospective[68, 1113, 15, 2832, 34, 35, 38, 40, 4246] cohort studies; the sample size ranged from 391 to 1056243, and the mean age of study ranged from 46.4 to 72.07. In DM ascertainment, 25 studies[6, 8, 9, 1115, 18, 19, …”
Section: Resultsmentioning
confidence: 99%
“…In DM ascertainment, 25 studies[6, 8, 9, 1115, 18, 19, 28, 29, 31, 3337, 3942, 4446] used the method of medical records, 5 studies[16, 20, 38, 43, 47] used the method of blood sugar test, and 6 studies[7, 10, 17, 27, 30, 32] used the method of self-reported. To avoid the effects of confounders, we preferred to extract the adjusted outcome effect estimates, but we still found that the outcome effect estimates of 4 studies were not adjusted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating epidemiologic evidence suggests that type 2 diabetes mellitus (T2DM) and/or certain diabetes treatments may be associated with prevalence, progression, or prognosis of some malignancies, but the risk may vary according to diabetes therapy and cancer site (Barone et al, 2008;Currie et al, 2012;Wang et al, 2013). For example, the cohorts of patients with T2DM were reported to have increased prevalence in several types of malignancies, such as liver, colorectal, pancreas, endometrial and breast cancers, etc (He et al, 2010;Wang et al, 2012;Elena et al, 2013;Zhang et al, 2013), and the all-cause mortality in patients with preexisting T2DM (preDM) was also increased in those with breast, prostate, pancreas and colorectal cancer, etc (Arif, et al, 2011;Currie et al, 2012;Hwang et al, 2013;Walker et al, 2013). Non-small-cell lung cancer (NSCLC) is the leading cause of cancer-related deaths worldwide (Siegel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%